Implementasi Program Mentoring untuk Menganalisis Tingkat Pemahaman Siswa Kelas X pada Materi Keanekaragaman Hayati - Ratu Celina Adinda; Alay Fia; Azmi, Aulia; Siti Rahma Aliyah; Sintia Erika Magdalena (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Schools play an important role in developing the intelligence of the younger generation, including intellectual, emotional, and spiritual aspects. An optimal learning process requires a balance between good teaching quality and a conducive learning environment. However, one of the obstacles in traditional learning is the lack of interaction between teachers and students, which is often caused by feelings of reluctance and shame. This condition hinders the effectiveness of learning. To overcome this problem, a mentoring program was implemented involving grade XII students as mentors for grade X students. In this program, grade XII students who understand the material help grade X students to learn. This study aims to examine the effect of the mentoring program on grade X students' understanding of Biodiversity material. This program is designed to create a more personal and supportive learning atmosphere, so that students feel more comfortable asking questions and discussing. The study was conducted using a quasi-experimental method with a pre-test posttest control group design. The results showed that the mentoring program significantly improved students' understanding of Biodiversity material. Therefore, this program can be an effective alternative to improve the quality of learning and improve student understanding.